Integrasi Sosial Dalam Membangun Keharmonisan Masyarakat - Kalsum, Afif Umi; Fauzan, Fauzan (Universitas Islam Negeri Raden Intan Lampung, 2019)
The realization of a harmonious community life is the goal of every country, including Indonesia. But increasing ethnic identity politics often breaks the harmony. So that the harmonious life of a pluralistic society has a high risk of social conflict. This field research aims to find out the forms of social integration and the factors that influence social integration in Pesawaran District, Lampung Province. Research data obtained by means of observation, interviews, and documentation. Then the data is analyzed descriptively-qualitatively with a sociological-political approach. The results showed that social integration in the community of Pesawaran Regency was normative - functional. Social integration occurs in the cultural dimension and socio-economic dimension. The factors that influence the formation of social integration include tolerance of society, equality of education and economics, geographical location of Pesawaran district, as well as the local wisdom of Lampung's indigenous people. This study concluded that social integration can be formed naturally through the values of wisdom owned by the community. Therefore, it is urgent to develop indigenous wisdom values that are owned by the community.